Estudio de factibilidad para la implementación de una app movil taxi service de transporte urbano para la Cooperativa “San Fernando” de la ciudad de Babahoyo. - Calero Carrera, Raúl Leonardo (2020)
In the present investigation, the Feasibility Study for the Implementation of a mobile app taxi service for urban transport for the Cooperativa "San Fernando" in the city of Babahoyo will be announced. As a first point, a brief background on the different App was made that exist such as mobile applications, smart phones, UniTaxi, Cabify, Uber platforms, because these are of vital importance for the development of the possible new implementation of the Taxi Service mobile app, it is worth mentioning that the concentration points of the unequal coordination of the taxi units, which is why it covers the days when there is the greatest traffic congestion, such as festivities, holidays, and peak hours. In addition, a technical, operational and economic feasibility study was carried out to verify whether the implementation of this mobile application for the use of the "San Fernando" Cooperative is feasible.